2021
DOI: 10.1167/tvst.10.6.29
|View full text |Cite
|
Sign up to set email alerts
|

Axial Length Change in Pseudophakic Eyes Measured by IOLMaster 700

Abstract: The purpose of this study was to investigate the change in axial length (AL) after cataract surgery measured by swept source optical coherence tomography (IOLMaster 700), and explore ways to eliminate this AL measurement error in pseudophakic eyes. Methods:Patients with cataract who underwent unilateral phacoemulsification with four types of intraocular lens (IOLs) implantation (Asphina 509M, Tecnis PCB00, enVista MX60, and Acrysof SN60WF) were enrolled. Bilateral AL measurements were performed before and 1 mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…15 The inconsistency in previous findings might be partly explained by the heterogeneity of study participants (phakic, aphakic, and pseudophakic) and surgical procedures. 22,23 Our study included a relatively In this study, we observed a trend that with longer AL, the IOLMaster 500 and IOLMaster 700 yielded larger differences between the preoperative and postoperative AL measurements (larger overestimation of true AL). We presume this is mainly due to a longer VCL with more SO tamponade and lack of appropriate further correction.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…15 The inconsistency in previous findings might be partly explained by the heterogeneity of study participants (phakic, aphakic, and pseudophakic) and surgical procedures. 22,23 Our study included a relatively In this study, we observed a trend that with longer AL, the IOLMaster 500 and IOLMaster 700 yielded larger differences between the preoperative and postoperative AL measurements (larger overestimation of true AL). We presume this is mainly due to a longer VCL with more SO tamponade and lack of appropriate further correction.…”
Section: Discussionmentioning
confidence: 74%
“…15 The inconsistency in previous findings might be partly explained by the heterogeneity of study participants (phakic, aphakic, and pseudophakic) and surgical procedures. 22,23 Our study included a relatively homogeneous study population who were all phakic and underwent only SO removal surgery (without combined cataract surgery), thus, it enabled a reliable evaluation and comparison of AL measurements among different devices.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is in accordance with several other reports. [12][13][14][15] The cause of the apparent shortening has been debated. As previously suggested, one explanation might be the index calibration of the IOLMaster readings; the dark horse being the crystalline lens, the refractive index of which is largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, constants optimization trough zeroing out the ME was performed for all formulas: new lens factors were all different from ULIB lens factors and some bias could be generated if optimized constants were used together with WK AL adjustments, that are projected for ULIB lens factor 35 . Another limitation of this study is that it was conducted with the IOLMaster 500 biometer, but considering the identification of a similar alteration in AL found before and after cataract extraction using the IOLMaster 700 36 and the good correlation between the measurement of AL with IOLMaster 500 and other optical biometers, it is possible to hypothesize the use of the correction factor of the preoperative AL similarly in other biometers 37 40 . In fact, in most recent studies regarding AL measurement comparison with different optical biometer, only small differences, often statistically significant but always < 0.03 mm, have been detected between IOLMaster 500 and other biometers 37 40 .…”
Section: Discussionmentioning
confidence: 99%